Differential herbivory and successional status in five tropical tree species - Néstor A. Mariano; Cristina Martínez-Garza; Raúl E. Alcalá (Revista Mexicana de Biodiversidad)
Using 4 restoration plots, we performed a common garden experiment to test the hypothesis that inter-specific variation in leaf herbivory depends on the successional status of tree species of the seasonally dry tropical forest. In July of 2011, we calculated the standing levels of herbivory in 5 species at the beginning of the rainy season: Ipomoea pauciflora (early-successional), Swietenia humilis, and Pseudobombax ellipticum (intermediate-successional) and Jacaratia mexicana and Bursera linanoe (late-successional). From each individual tree, we selected 14 leaves to measure herbivory (N = 84 plants, 821 leaves). The mean leaf area lost by herbivory across the 5 tree species was 5.25%. The results evidencing differences among the categories evaluated supported our hypothesis, as herbivory increased from the late to the early-successional species. We discussed the proximate (i.e, differential leaf traits) and ultimate causes (i.e., differential selective pressures) operating on trees situated at the extreme of the successional stages that could explain the inter-specific differences in herbivory we observed. In accordance with our results, successional status should be recognized as a factor affecting herbivory in tree species in tropical dry forests.